Design of a Multi-Layered Reconfigurable Frequency Selective Surface Using Water Channels - Son, Dong Chan; Shin, Hokeun; Kim, Yoon Jae; Hong, Ic Pyo; Chun, Heoung Jae; Choo, Hosung; Park, Yong Bae (Journal of Electrical Engineering and Technology, 2019)
In this study, we propose a multi-layered reconfigurable frequency selective surface (FSS) using water channels, which can be switched between the bandpass and bandstop states. Variation ratio in transmission between the bandpass and bandstop states is drastically improved by multi-layer dielectric slabs with water channels. We then fabricate the design, and the measured results in the X-band shows a good agreement with the simulation. The variation in transmission coefficients between the two states increases from 0.34 to 0.71 using the 5-layered dielectric slabs with water channels, which verifies the reconfigurability of the proposed FSS.
Keywords: Dielectric slabs; Measured results; Multi-layered; Multilayer dielectrics; Reconfigurability; Reconfigurable frequency selective surfaces; Transmission coefficients; Water channels; Frequency selective surface; Water channels